Comparison of eating habits and gut microbiota of preschool children with obesity - Shymaa M. Al-Jabri; Effat A. Al-Judaibi; Yasser A. Al-Gamdee; Awatif A. Al-Judaibi (Exploration of Medicine, 2023)
Aim: Childhood obesity is a global health concern that affects the daily life of children. It has a complex pathogenesis that involves genetic and nutritional factors among others. Moreover, the dysbiosis of gut microbiota has been recently associated with the development and progression of obesity. Methods: A total of 43 faecal samples were collected from Saudi children; among them, 26 were normal and 17 were obese. Whole genomic DNA was extracted from their faecal samples and sequenced using an Illumina Sequencing platform. Results: The gut microbiota was dominated by Phyla Firmicutes (69.00%) and Bacteroidetes (20.00%), followed by Actinobacteria (8.50%). In children with obesity, the abundance of Firmicutes was decreased, while Bacteroidetes was relatively enriched. Verrucomicrobia and Proteobacteria were not detected in the obese group, but they were found in low abundance in the control group. Phylum Firmicutes was dominated by the families Ruminococcaceae (17.86%) and Lachnospiraceae (41.20%). Less Ruminococcaceae was found in the obese group. Phylum Bacteroidetes was dominated by families Bacteroidaceae (12.98%) and Prevotellaceae (4.10%), which were enriched in the obese group. Genus Blautia (14.29%) was highly abundant, followed by Bacteroides (12.98%), Faecalibacterium (10.08%), Bifidobacterium (7.96%), and Prevotella (5.04%). Ruminococcus_g2 and _g4, Subdoligranulum, Roseburia, Fusicatenibacter, Anaerostipes, and Faecalibacterium were decreased (P > 0.05) in the obese group, while Streptococcus, Agathobacter, Prevotella, Bacteroides, and Bifidobacterium were increased (P > 0.05). Conclusions: In conclusion, a diverse bacterial community was profiled in Saudi preschool children, and changes in bacterial community composition were observed between obese- and normal-weight children.